EFEKTIVITAS EKSTRAK KULIT DAN PERASAN JERUK LEMON (CITRUS LIMON L.) SEBAGAI INSEKTISIDA TERHADAP NYAMUK AEDES AEGYPTI - Wibisono, Freshinta Jellia; Deo, Amelia Alfatiani Putri de; Rahmawati, Indra; Sasmita, Rochiman (VITEK : Bidang Kedokteran Hewan, 2023)
This study aims to determine the effectiveness of natural insecticides of lemon peel extract and lemon juice (Citrus limon L.) against the death of the Aedes aegypti mosquito. The experimental animals in this study were 600 Aedes aegypti mosquitoes. This type of research is an experimental study with the Complete Randomized Design method using 8 treatments and 3 replications. The treatment group consisted of positive control (Transflutrin), negative control (Aquadest), and lemon peel extract and juice (Citrus limon L.) with concentrations of 30%, 35% and 40%. Observations were made every 15 minutes for 1 hour exposure. The results showed that 30% lemon peel extract was able to kill 58.33% mosquitoes, a concentration of 35% was able to kill 78.33% mosquitoes and concentration of 40% was able to kill 86.66% mosquitoes. Lemon juice 30% can kill 25% mosquitoes, 35% concentration can kill 33.33% mosquitoes, and 40% concentration can kill 40% mosquitoes. Based on the results of the study, treatment using lemon peel extract at various concentrations had an effect on mosquito mortality, with the highest mortality reaching 86.6%. The treatment using lemon juice at various concentrations had no effect on mosquito mortality, with the lowest mortality being 25%. The results of the one way ANOVA calculation obtained P-value = 0.00 (P ≤ 0.05) means that there is a significant difference in the number of mosquitoes that die between treatment groups. Duncan's test results showed that lemon peel extract concentrations 30%, 35%, and 40% were the most effective concentrations compared to lemon juice. The conclusion of this study was lemon peel extract (Citrus limon L.) effective as a natural insecticide against Aedes aegypti mosquitoes.